The Effects of Inflation, Interest Rates and Exchange Rates on Composite Stock Price Index During the Covid-19 Pandemic - Nurmasari, Ifa; Nur'aidawati, Siti (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2021)
The COVID-19 pandemic that hit Indonesia and even the world, caused changes in various sectors and decline in the Indonesian economy. To improve the economy, it is necessary to increase investment. This research aims to find out how the influence of inflation, bank interest rates and currency rates on Composite Stock Price Index both partially and simultaneously at the time of the covid-19 pandemic. The research method used in this study is quantitative descriptive, which discusses the problems faced that describe the state of a country expressed in numbers. The data used in this study is secondary data. It was taken during the covid-19 period from March 2020 to July 2021. The analytical methods are used multiple linear regression, classical assumption test, hypothesis test, and determination coefficient test. The novelty of this research is to use macroeconomic data during the COVID-19 pandemic. The results showed that simultaneously, inflation, bank interest rates, and currency rates had a significant effect on Composite Stock Price Index. Inflation, bank interest rates, and currency rates exert a 94.9% effect on Composite Stock Price Index. The remaining 5.1% was affected by other factors not used in the study. Partially, inflation is positive and significant to Composite Stock Price Index. Bank interest rates and currency rates negatively and significantly affect Composite Stock Price Index.